2020
DOI: 10.1186/s42836-020-00028-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between barbed suture and conventional suture in total knee arthroplasty: a systematic review and meta-analysis

Abstract: Objective: The aim of this systematic review and meta-analysis was to evaluate the efficacy of barbed versus conventional sutures in total knee arthroplasty. Methods: Two investigators independently performed data extraction and assessed study quality using the keywords "barbed suture, wound suture, total knee arthroplasty" in two search trials, individual trials, and trials from Systematic Reviews or Meta-analyses in PubMed, Cochrane Library, Web of Science, and EMBASE databases. Result: A total of 11 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Wird die Oberfläche der Nahtmaterialien mit Widerhaken
Widerhaken
versehen, die so angeordnet sind, dass sie beim Einstechen an der Oberfläche anliegen, bei entgegengesetzter Bewegung heraustreten, kann auf Knotung verzichtet werden [ 13 , 14 , 15 ]. Andere Autoren weisen auf die Zeitökonomie beim Einsatz dieser Materialien hin [ 16 , 17 , 18 ] und auf ein geringeres Gesamtkomplikationsrisiko bei (arthroskopischen) Knieoperationen [ 18 ].…”
Section: Auswahl Des Nahtmaterialsunclassified
“…Wird die Oberfläche der Nahtmaterialien mit Widerhaken
Widerhaken
versehen, die so angeordnet sind, dass sie beim Einstechen an der Oberfläche anliegen, bei entgegengesetzter Bewegung heraustreten, kann auf Knotung verzichtet werden [ 13 , 14 , 15 ]. Andere Autoren weisen auf die Zeitökonomie beim Einsatz dieser Materialien hin [ 16 , 17 , 18 ] und auf ein geringeres Gesamtkomplikationsrisiko bei (arthroskopischen) Knieoperationen [ 18 ].…”
Section: Auswahl Des Nahtmaterialsunclassified
“…On the one hand, emerging adverse events associated with barbed sutures were identified in long follow-up visits. For example, a systematic review and meta-analysis reported higher incidence of suture breakage, which might require additional surgical interventions, thereby leading to an escalation in medical waste generation and economic loss 6 . On the other hand, effectiveness and safety seem to be controversial.…”
Section: Introductionmentioning
confidence: 99%